(untitled) (KYAMC Journal, 2018)
Background: The growth of infants born to diabetic mothers is at greater risks because of their pregnancy related complications. Objectives: This study concerns comparison of BMI changes in different periods of infants born to pre-diabetic mothers (DM) and gestational diabetic mothers (GDM) with control infants born to apparently healthy non-diabetic mothers (NDM). Materials & Methods: This study comprising 251 newbornmother pairs (n: DM=86; GDM=86 and NDM=79) recruited from the Bangladesh Institute of Research and Rehabilitation in Diabetes, Endocrine and Metabolic Disorders (BIRDEM), Dhaka. Results: BMI at birth was significantly higher for DM (BMI: 13.3±0.2 vs.12.6±0.2; p=0.003) and GDM (BMI: 13.7±0.2 vs.12.6±0.2; p<0.001) groups compared to the NDM group. On paired t tests, BMI increased significantly during 0-3 month period and 3-6 months periods in all groups (DM, GDM and NDM). At 0 month, compared to babies in the NDM group, mean BMI z-scores were significantly higher for the DM (-0.095±1.2 vs. -0.73±1.4; p=0.003) and GDM (0.16±1.4 vs.-0.73±1.4; p<0.001) groups. On paired-samples t tests, BMI Z-scores decreased from birth to 3 month of age in DM and GDM groups, but this decrease was significant for the GDM group only. In subsequent periods, BMI z-scores increased in all groups but the increment was more evident in GDM and NDM groups. Conclusion: At 0 month (birth), compared to babies in the NDM group, mean BMIs were significantly higher for the DM and GDM groups which became normalised by 3rd month when they got rid of maternal metabolic influences. The changes in BMI Z-score during 9-12 months period were significantly positive for NDM group compared to others. KYAMC Journal Vol. 8, No.-2, Jan 2018, Page 13-17